Insight into the Effects of Sous Vide on Cathepsin B and L Activities, Protein Degradation and the Ultrastructure of Beef - Yin, Yantao (Foods, 2020)
This study aimed to evaluate the effects of sous vide cooking (SV) on beef tenderness and its underlying potential mechanism. Beef semimembranosus (SM) were subjected to SV treatments at 45 °C, 55 °C and 65 °C for 4 h. Compared with control samples (CK, cooked at 75 °C until a core temperature of 72 °C was attained), SV treatment significantly promoted the release of cathepsin B and cathepsin L from lysosomes and decreased the shear force of beef SM (p < 0.05). In comparison with CK, samples treated with SV had more hydrolysis of myosin heavy chain and obtained higher myofibrillar fragmentation index, collagen solubility as well as longer sarcomere length (p < 0.05). The current study showed that the proteolysis of myofibrillar protein and collagen induced by cathepsin B and cathepsin L, and the limited longitudinal shrinkage together contributed to the improvement of beef tenderness upon SV.